2. Considere a seguinte expressão
algébrica:
(-a - b)(a + b) + ab³- a²/b
Sendo a = b = -2, o valor numérico dessa expressão é:
a) 2 b)-2 c)1 d)-1 e)4
Soluções para a tarefa
Respondido por
11
Explicação passo-a-passo:
(-a - b)(a - b) + ab^3 - a^2/b =
(-(-2)-(-2))(-2-(-2)) + (-2)(-2)^3 - (-2)^2/(-2) =
(2 + 2)(-2 + 2) + (-2)(-8) - 4/(-2) =
4.0 + 16 + 2 =
0 + 18 =
18
Perguntas interessantes
História,
9 meses atrás
Matemática,
9 meses atrás
Geografia,
9 meses atrás
Matemática,
11 meses atrás
Inglês,
11 meses atrás
Física,
1 ano atrás